2017
DOI: 10.1007/s40843-017-9138-1
|View full text |Cite
|
Sign up to set email alerts
|

Layered double hydroxides with larger interlayer distance for enhanced pseudocapacitance

Abstract: The interlayer space of the layered materials is not always the electrochemical active area for contributing to the pseudocapacitive process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The SEM results show that the morphology of the Co-adsorbed LDH is mostly an anomalistic lamellar structure with a coarse surface, that is poriferous and of a seaweed-like structure, and therefore it is different from the original LDH. Furthermore, the inter-lamellar spacing distance is sensitive to the structure variations between amorphous and crystalline LDH, which are also usually regarded as criteria for the cation adsorption capacity [ 21 , 22 ]. Consequently, the crystal structure evolution of CaAl-Cl-LDH before and after cobalt adsorption, including the phases, boundaries of the grains, and the domains, are investigated in Figure 4 using a high-resolution transmission electron microscope (HR-TEM).…”
Section: Resultsmentioning
confidence: 99%
“…The SEM results show that the morphology of the Co-adsorbed LDH is mostly an anomalistic lamellar structure with a coarse surface, that is poriferous and of a seaweed-like structure, and therefore it is different from the original LDH. Furthermore, the inter-lamellar spacing distance is sensitive to the structure variations between amorphous and crystalline LDH, which are also usually regarded as criteria for the cation adsorption capacity [ 21 , 22 ]. Consequently, the crystal structure evolution of CaAl-Cl-LDH before and after cobalt adsorption, including the phases, boundaries of the grains, and the domains, are investigated in Figure 4 using a high-resolution transmission electron microscope (HR-TEM).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies on LDHs have shown that replacing the original interlayer anions with an organic anionic surfactant has a positive effect on the increase of the interlayer spacing. [ 28,64,65 ] For a dual charge storage mechanism integrated with surface redox, ion intercalation is an effective strategy for the chemical modification of LDH‐based supercapacitors. Lin et al [ 28 ] synthesized NiCo‐LDH nanosheets with large interlayer spacing via the intrinsic pillar effect of sodium dodecylbenzene sulfonate (NiCo‐SDBS‐LDH), as shown in Figure 5c.…”
Section: Chemical Modification Of Ldhsmentioning
confidence: 99%
“…Doping or partially substituting with other metal ions, such as Mg [21,22], Al [23][24][25][26], Mn [27], Fe [4], Co [28][29][30][31][32] or Zn [33] in α-Ni(OH) 2 has found to be an effective way to stabilize the crystal structure; the resulting complex nickel hydroxides have demonstrated much improved electrochemical properties and performance when used as electrodes in supercapacitors. For example, α-phase NiCoMn hydroxide demonstrated high power densities and high energy [34], CoAl hydroxide possessed enhanced electrochemical performance [35,36]. Among these metal ions, Mg is an alkaline-earth metals with smaller atomic weight.…”
Section: Introductionmentioning
confidence: 99%